Real-world treatment patterns and clinical outcomes in patients receiving palbociclib combinations for HR+/HER2– advanced/metastatic breast cancer in Japan: Results from the IRIS study. (2022) - Mycock, Katie; Zhan, Lin; Hart, Kieran; Taylor-Stokes, Gavin; Milligan, Gary; Atkinson, Christian; Mitra, Debanjali
Highlights: In Japan, palbociclib is recommended for HR+/HER2- advanced breast cancer patients. This was a retrospective chart review study of palbociclib in 170 Japanese patients. 12-month progression-free rates: 85% first line; 56% second or later line. 12-month survival rates: 99% first line; 94% second or later line. Japanese IRIS findings are reflective of Japanese PALOMA patients (Mukai 2019). Abstract: Background: The incidence of breast cancer is rising in Japan, particularly in postmenopausal women. The CDK 4/6 inhibitor palbociclib has demonstrated efficacy in clinical studies in patients with hormone receptor-positive (HR+), human epidermal growth factor 2 (HER2)-negative advanced/metastatic breast cancer (ABC/MBC). The Ibrance Real World Insights (IRIS) study (NCT03159195) collected real-world data for palbociclib-treated patients in several countries including Japan, where such data are currently scarce. Methods: : IRIS was a retrospective chart review study of patients with confirmed HR+/HER2- ABC/MBC receiving palbociclib according to approved indications in real-world clinical practice. In Japan, physicians each abstracted data from patient medical records for up to eight sequential patients treated with palbociclib plus an aromatase inhibitor ( P +AI) or fulvestrant ( P + F) . Outcomes included progression-free rates (PFRs) and survival rates (SRs). Results: Fifty-eight physicians abstracted data for 170 patients receiving palbociclib in the first (64.1%) or second or later line (35.9%), in combination with AI (51.2%) or fulvestrant (48.8%). Median follow-up was 10.4 months. Most patients were initiated on palbociclib 125 mg/d ( P +AI, 63.2%; P + F, 78.3%). PFRs at 12 and 24 months were 76.2% and 52.6%, respectively, for P +AI and 71.6% and 65.6%, respectively for P + F. PFRs at 12 and 24 months were 85.4% and 66.5%, respectively, for first-line palbociclib combinations and 56.4% and 50.7%, respectively, for second- or later-line palbociclib combinations. Conclusions: : In this analysis of the Japanese IRIS cohort, outcomes in terms of PFRs and SRs appear to be better with first- versus second or later-line palbociclib, regardless of the endocrine partner.